2003
DOI: 10.1177/0163278702250093
|View full text |Cite
|
Sign up to set email alerts
|

Validation Of An Observation Instrument For Measuring Student Engagement In Health Professions Settings

Abstract: Documenting student engagement has received increased emphasis in medical schools, as teaching strategies are changing to include more student-to-student interactions. The purpose of this study was to develop and evaluate a measure of student engagement completed by independent observers that would not interfere with student learning time. Data from 3,182 observations completed by nine observers in 32 educational classroom settings with 23 different instructors were used to evaluate the interobserver reliabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 11 publications
1
71
0
Order By: Relevance
“…Even so, we are confident in the data collected for this study by our seven well-trained observers, given the careful protocol adherence and resulting high inter-observer consistency they demonstrated in the STROBE development study 18. …”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Even so, we are confident in the data collected for this study by our seven well-trained observers, given the careful protocol adherence and resulting high inter-observer consistency they demonstrated in the STROBE development study 18. …”
mentioning
confidence: 76%
“…As an alternative small group-based instructional strategy, team learning has been widely implemented in business and science education. 17,18 In a typical team learning implementation, learners independently study outside of class to master identified content-related objectives. Groups then complete specially designed, in-class application assignments that promote collaboration and application of important concepts.…”
Section: Description Of Team Learningmentioning
confidence: 99%
“…Observers also recorded whether these behaviors are directed at (or in response to) the instructor, a group of students, one other student, or themselves (e.g., writing or reading). Because of the availability of other datasets using the observation instrument, 19 we are able to compare the pattern of interactions recorded during the EBM course to the pattern of interactions recorded during sessions of six other team learning-based courses and eight didactic lecture-based courses taught at Baylor.…”
Section: Course Evaluation Methodsmentioning
confidence: 99%
“…A total of 9 of the 12 items were taken from an existing engagement survey. 11 Surveys measured resident involvement, contribution, participation, and engagement, and included comments that were…”
Section: Survey Administrationmentioning
confidence: 99%